INDONESIANS’ TENDENCY TO REFER ABBREVIATION AS ACRONYM: TYPES OF ABBREVIATION AS WORD FORMATION PROCESS - Tatum Derin; Susy Deliani; Nurul Fauziah; Nur Afifah; Budianto Hamuddin (Universitas Muhammadiyah Tangerang, 2019)
The purpose of this research is to analyze the tendency of Indonesians to assume all types of abbreviation is acronym. This study examines the types of word formation process of abbreviation, and whether abbreviation or acronym is the correct umbrella term for this particular morphological process. Using library research method, this paper refers to two key morphology researchers from Britain and Indonesia, Laurie Bauer and Harimurti Krisdalaksana respectively, as well as one Indonesian Doctorate Arie Ansrasyah Isa whom referred the former two researchers in her study that proposes 16 types of abbreviations using data from top Indonesian newspapers, Jakarta Post and Kompas. This paper concludes that common people in Indonesia refer all abbreviations as acronyms because their high preference in abbreviating long phrases stems from the desire to increase pronounceability and familiarity of words, usually in the context of humor, but is highly prevalent in all situations, formal or non-formal.